2004
DOI: 10.1136/hrt.2003.011650
|View full text |Cite
|
Sign up to set email alerts
|

The forces generated within the musculature of the left ventricular wall

Abstract: Objectives: To test the hypothesis that two populations of myocardial fibres-fibres aligned parallel to the surfaces of the wall and an additional population of fibres that extend obliquely through the wall-when working in concert produce a dualistic, self stabilising arrangement. Methods: Assessment of tensile forces in the walls of seven porcine hearts by using needle probes. Ventricular diameter was measured with microsonometry and the intracavitary pressure through a fluid filled catheter. Positive inotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 18 publications
4
93
0
Order By: Relevance
“…Thompson et al (Thompson et al, 2010a) showed in D. pealeii that the inner surface of the mantle experiences 1.3 to 1.6 times greater circumferential strain than the outer surface at any time point during the exhalant phase of a jet. Because circular fibers are oriented in transverse planes of the mantle and also appear to follow a perfectly circumferential trajectory, there are no architectural specializations, such as those found in mammalian cardiac ventricle muscle (Lunkenheimer et al, 2004;Anderson et al, 2006;Anderson et al, 2009) or vertebrate skeletal muscles (Alexander, 1969;Rome and Sosnicki, 1991;Wakeling and Johnston, 1999;Azizi et al, 2008) that could permit all of the fibers to experience approximately the same range of strains during jetting. Thus, the transmural gradient of circumferential strain in the mantle may require muscle fibers from the inner surface to operate farther left on the ascending limb of the length-tension curve at any instant during mantle contraction.…”
Section: Mantle Kinematics and In Vivo Muscle Operating Length Rangementioning
confidence: 99%
“…Thompson et al (Thompson et al, 2010a) showed in D. pealeii that the inner surface of the mantle experiences 1.3 to 1.6 times greater circumferential strain than the outer surface at any time point during the exhalant phase of a jet. Because circular fibers are oriented in transverse planes of the mantle and also appear to follow a perfectly circumferential trajectory, there are no architectural specializations, such as those found in mammalian cardiac ventricle muscle (Lunkenheimer et al, 2004;Anderson et al, 2006;Anderson et al, 2009) or vertebrate skeletal muscles (Alexander, 1969;Rome and Sosnicki, 1991;Wakeling and Johnston, 1999;Azizi et al, 2008) that could permit all of the fibers to experience approximately the same range of strains during jetting. Thus, the transmural gradient of circumferential strain in the mantle may require muscle fibers from the inner surface to operate farther left on the ascending limb of the length-tension curve at any instant during mantle contraction.…”
Section: Mantle Kinematics and In Vivo Muscle Operating Length Rangementioning
confidence: 99%
“…These are the cardiomyocytes believed by Krehl [18] to provide the driving force for ventricular emptying. Perhaps more importantly, the quantitative, as opposed to qualitative, observations we were able to make using an automated system that avoids the need for subjective interpretation [16] confirm that a significant proportion of cardiomyocytes are aligned in a transmural fashion across the ventricular walls [11]. These measurements provided no support for the notion that all cardiomyocytes are aligned in a virtually tangential fashion.…”
Section: Histological Findingsmentioning
confidence: 69%
“…The marked heterogeneity in the extent of aggregation of the individual cardiomyocytes, furthermore, indicates a local "fingerprint" for each ventricular region, these regions representing the "segments" as identified echocardiographically [17], thus pointing to the well-recognized regional variability in antagonistic function of the wall [11, 12, 20 -22]. The simultaneous coexistence of dilating and constrictive activity in the ventricular myocardium was measured previously, a feature which prevails throughout the cardiac cycle [11]. We suggest that this mechanism, which was described as antagonism, is designed to control the mean ventricular shape and size.…”
Section: Histological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A, left). According to direct force measurements, tangential netting components generate the unloading type of force signal, which slowly decays after having reached an early systolic peak (11). This signal proves to be relatively insensitive to negative inotropic therapy (10).…”
Section: Discussionmentioning
confidence: 99%